Improving the Ability to Read the Qur'an Through Qiro'ati Method - Khoerunnisa, Ika; Effendi, Muhamad Ridwan; Syaprudin, Didin (Proceeding International Conference on Islam and Civilization (ICONIC), 2021)
This researcher aims to determine 1) The ability to read the Qur'an of DTA Al-Hikmah students. 2) To find out the implementation of the Qiroati method in improving the ability to read the Qur'an at Al-Hikmah DTA. 3) To find out the improvement of the ability to read the Qur'an through the Qiroati method in DTA Al-Hikmah. 4) To find out the results obtained in improving the ability to read the Qur'an through the Qiroati Method at Al-Hikmah DTA. The method used in this study is a research with a Quisi Experiment approach. This experiment is also known as a quasi-experiment. Experimental research is one type of quantitative research that is very strong for measuring causal relationships. The total population of AlHikmah DTA students is 60, and the number of samples in this study were 30 students drawn from the total population of Al-Hikmah DTA students. The theory used in this research is Rahim and KH Dahlan Salim Zarkasy. Based on the results of data analysis after treatment (Post test) with a t-test (t-test), namely the independent samples test. From the test, it was shown that the students' ability to read the Qur'an in the experimental class and the control class at the time of the post-test, it is known that the tcount is 4.612 with a significance of 0.000. The value of sig (2-tailed) < 0.05, then there is a difference because the significant value is less than 0.05. It is known that t count is 4.612 from df 28 with 0.05. Then found t table of 2.048, thus t count of 4.612 > t table 2.048, then based on the conclusion that H0 is rejected and Ha is accepted, which means that there is a difference in the average results of students' ability to read the Qur'an during the pre-test and post-test. In other words, the qiroati method with the usual method will produce different results for students' abilities. This is also supported by the mean value of the experimental class which is 71.67, which is greater than that of the control class, which is 51.08. So it can be concluded that the results of students' ability to read the Qur'an in the experimental class can be increased after using the Qiro'ati method.